The approach to solving the problem of optimization of transportation - Litvynov, V.V.; Skakalina, О.V. (Математичні машини і системи, 2015)
There was discussed the problem of optimization of logistics processes for agri-industrial sector. The article discusses the complete cycle of development of logistics flow. Based on the analysis of the integrated indicators of the national agricultural holdings there were proposed model of the ordering process of transportation and the computational scheme for solving the problem. Розглядається проблема оптимізації логістичних процесів для господарюючих суб’єктів агропромислового сектора. У статті розглядається повний цикл формування логістичного потоку. На основі аналізу інтегрованих показників діяльності національних агрохолдингів запропоновані модель процесу упорядкування транспортних перевезень та обчислювальна схема рішення задачі. Рассматривается проблема оптимизации логистических процессов для хозяйствующих субъектов агропромышленного сектора. В статье рассматривается полный цикл формирования логистического потока. На основе анализа интегрированных показателей деятельности национальных агрохолдингов предложены модель процесса упорядочения транспортных перевозок и вычислительная схема решения задачи.